Moderating Effect of Motivation on factors affecting Audit Quality - Nanda Putra Saragi; Idhar Yahya; Abdhy Aulia Adnans (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to evaluate the effect of auditor competence, auditor experience, and remote audit on audit quality with motivation as a moderating variable in the Internal Audit Unit of PT. TASPEN (Persero) Jakarta. The population and sample in this study were 30 respondents, spread over the Internal Control Unit of PT TASPEN (Persero) in Jakarta, and the Internal Control Unit in the regions such as SPIDA Bandung, SPIDA Jakarta, SPIDA Makassar, SPIDA Medan, SPIDA Semarang. The data is processed by PLS Algorithm analysis with the help of Smart PLS 3.0. Based on the results of this study, it shows that the experience of auditors has a positive effect on audit quality, remote audit has a positive effect on audit quality, and competence has no effect on audit quality of the Internal Audit Unit of PT. TASPEN (Persero) Jakarta. Meanwhile, motivation as a moderating variable, unable to moderate the relationship between auditor competence and audit quality, unable to moderate the relationship between auditor experience and audit quality, and unable to moderate the relationship between remote audit on audit quality.